2013
DOI: 10.1371/journal.pone.0058065
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characteristics of Neisseria meningitidis Disease-Causing Strains in Argentina, 2010

Abstract: Phenotypic and genotypic characterization of 133 isolates of Neisseria meningitidis obtained from meningococcal disease cases in Argentina during 2010 were performed by the National Reference Laboratory as part of a project coordinated by the PAHO within the SIREVA II network. Serogroup, serotype, serosubtype and MLST characterization were performed. Minimum Inhibitory Concentration to penicillin, ampicillin, ceftriaxone, rifampin, chloramphenicol, tetracycline and ciprofloxacin were determined and interpreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 43 publications
(45 reference statements)
2
34
0
1
Order By: Relevance
“…El análisis genético de las cepas reveló que el complejo clonal ST-11 es el predominante en el serogrupo W, como ya se había reportado anteriormente 58 . Este complejo se relaciona con los clones identificados en la epidemia ocurrida durante la peregrinación a La Meca en los años 2000-2001, clon que se exportó a diferentes países [59][60][61] . Este clon también ha sido identificado como un clon hipervirulento, lo cual coincide con lo sucedido en Chile, donde los casos de EMI se han manifestado como cuadros graves, principalmente meningococcemias, y con una alta letalidad 41,62 .…”
Section: Resultsunclassified
“…El análisis genético de las cepas reveló que el complejo clonal ST-11 es el predominante en el serogrupo W, como ya se había reportado anteriormente 58 . Este complejo se relaciona con los clones identificados en la epidemia ocurrida durante la peregrinación a La Meca en los años 2000-2001, clon que se exportó a diferentes países [59][60][61] . Este clon también ha sido identificado como un clon hipervirulento, lo cual coincide con lo sucedido en Chile, donde los casos de EMI se han manifestado como cuadros graves, principalmente meningococcemias, y con una alta letalidad 41,62 .…”
Section: Resultsunclassified
“…Argentina has experienced an increase on W135 cases since 2008, and recently reported that nearly 49% of disease isolates characterized by their National Reference Laboratory in 2010 belonged to this serogroup. Brazil also reported an outbreak of disease caused by W135 in Southern provinces, in the border with Argentina [19], [28], [29]. In both countries the strain has been identified as the W135:P1.5,2:ST-11.…”
Section: Discussionmentioning
confidence: 99%
“…Data on serogroup distribution in Latin America and Caribbean countries is scarce. However, those obtained through the SIREVA II network indicates that although serogroups B and C are the main cause of IMD in the region, serogroup Y and specially W135 have increased in recent years [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of CC11 strains associated with serogroup W in Africa represents an example of expansion of a successful clone. The epidemic with phenotype W:2a:P1.5,2 was identified in 2001 as being associated with the Hajj pilgrimage, with disease emerging throughout Europe, and, in the last few years, in Argentina and other countries in Latin America [65,175,176]. CC8 complex (formerly cluster A4), genetically related to CC11, was also mainly associated with serogroup C disease [122], was first identified in the Netherlands in 1961 [44] and has been a common cause of disease since 1970s [24,177,178], although in the last years strains belonging to CC8 have decreased worldwide (source: EU-IBIS).…”
Section: Clonal Complex 32 Outbreaksmentioning
confidence: 99%